Innovative rubber technologies for sensitive sectors - Setua D K (Rubber Asia, 2013)
The ongoing R&D initiatives of the Defence , Aerospace and Atomic Energy sectors emphasize developement of functional and smart poplymeric devices to improve efficacy of the conventional equipement. Moreover, they are also part of these sectors efforts to demonstrate indigenous technological capability to earn global reputation and leadership
Keywords: Rubber technology